Risk evaluation of a future B2B cell factory process producing cellular agriculture ingredients - Välisalo, Tero; Salo, Satu; Wessberg, Nina; Ritala, Anneli; Säämänen, Arto (Frontiers in Sustainable Food Systems, 2025)
Cellular agriculture can help to meet the growing global demand for proteins and other food products by producing, e.g., single-cell protein (SCP) through fermentation, simultaneously enhancing sustainability and resource efficiency. However, our path toward 2040 may involve crises related to energy, water and raw material availability, contaminated production processes, logistics or increased costs. In this study, we assessed the risks of a cell factory operating in 2040, which could face challenges such as freshwater shortages, power outages, and scarcity of chemicals and other materials. The envisioned cell factory utilises various side streams as raw materials and operates in an urban area. We employed the qualitative HAZSCAN (Hazardous Scenario Analysis) method to assess the occupational, product, and environmental safety of a fully operational hypothetical business to business (B2B) cell factory producing cellular agriculture ingredients. The analysis was conducted by a working group, including experts from VTT and industrial representatives, through five focused meetings to prepare activity and process model, systematically identify hazards, and estimate their severity and probability. Risk was then classified using a tailored risk matrix. Hazards causing production interruptions, impairment to occupational health and product safety, as well as environmental safety, were identified and their risks were assessed. Future risks may arise from resource scarcity, the quality of raw materials or logistical issues related to raw materials. Risks related to utilities stem from the availability of electricity, steam, or water. Operational risks can originate from maintenance challenges, process quality control, storage and handling of materials, insufficient instructions for operators, and potential leaks into the environment. Additionally, risks may be caused by disruptions in information transfer or vandalism. The analysis emphasised the need for comprehensive safety and risk management methods that consider both process safety and environmental impacts.